IGFBP-1 Expression Promotes Tamoxifen Resistance in Breast Cancer Cells via Erk Pathway Activation - Zheng, Yan; Sowers, Janel Y.; Houston, Kevin D. (Frontiers in Endocrinology, 2020)
Insulin-like growth factor (IGF) system plays a significant role in many cellular processes, including proliferation and survival. In estrogen receptor positive breast cancer, the level of circulating IGF-1 is positively associated with the incidence and at least 50% of cases have elevated IGF-1R signaling. Tamoxifen, a selective estrogen receptor modulator and antagonist for estrogen receptor alpha (ERα) in breast tissue, is a commonly prescribed adjuvant treatment for patients presenting with ERα-positive breast cancer. Unfortunately, tamoxifen resistance is a frequent occurrence in patients receiving treatment and the molecular mechanisms that underlie tamoxifen resistance not adequately defined. It has recently been reported that the inhibition of IGF-1R activation and the proliferation of breast cancer cells upon tamoxifen treatment is mediated by the accumulation of extracellular insulin-like growth factor binding protein 1 (IGFBP-1). Elevated IGFBP-1 expression was observed in tamoxifen-resistant (TamR) MCF-7 and T-47D cells lines suggesting that the tamoxifen-resistant state is associated with IGFBP-1 accumulation. MCF-7 and T-47D breast cancer cells stably transfected with and IGFBP-1 expression vector were generated (MCF7-BP1 and T47D-BP1) to determine the impact of breast cancer cell culture in the presence of increased IGFBP-1 expression. In these cells, the expression of IGF-1R was significantly reduced compared to controls and was similar to our observations in tamoxifen-resistant MCF-7 and T-47D cells. Also similar to TamR breast cancer cells, MCF7-BP1 and T47D-BP1 were resistant to tamoxifen treatment, had elevated epidermal growth factor receptor (EGFR) expression, increased phospho-EGFR (pEGFR), and phospho-Erk (pErk). Furthermore, tamoxifen sensitivity was restored in the MCF7-BP1 and T47D-BP1 upon inhibition of Erk phosphorylation. Lastly, the transient knockdown of IGFBP-1 in MCF7-BP1 and T47D-BP1 inhibited pErk accumulation and increased tamoxifen sensitivity. Taken together, these data support the conclusion that IGFBP-1 is a key component of the development of tamoxifen resistance in breast cancer cells.